PELATIHAN PEMASARAN EKSPOR MELALUI INTERNET BAGI UKM DI KALIMANTAN SELATAN - Achmad Aditya Ashadul Ushud; Ita Novita; Subandi Subandi (P3M Politeknik Negeri Malang, 2020)
UKM products in Indonesia have enormous potential to penetrate the export market. By doing exports, UKM have the potential to get bigger profits, because their market will become wider. The problem is, there are still many who don't know and understand how to market their products abroad. The internet offers great opportunity for local products to be widely known globally. By using good strategy, the internet can become a main market for UKM in marketing their products. In collaboration with Dinas Perdagangan Provinsi Kalimantan Selatan and the Regional Government, a training was created to introduce the internet as a promotional medium for UKM to expand their market. This internet product marketing training for UKM in South Kalimantan is one way of introducing and sharing knowledge how to market products via the internet. Most UKM, especially those in South Kalimantan, don't know yet how to promote their products via the internet. The enthusiasm of UKM players who wish to be able to export their products was seen during the training. The first target country to aim for is ASEAN countries.